1998
DOI: 10.4315/0362-028x-61.9.1143
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Sporulation, Enterotoxin Production, and Protein Synthesis by Clostridium perfringens Type A Following Heat Shock

Abstract: Application of a heat shock (43 to 50 degrees C) applied early during the sporulation process of Clostridium perfringens delayed spore and enterotoxin production. Final levels of heat-resistant spores were similar to the control, but enterotoxin levels were reduced when the heat shock was applied at the third hour of incubation. The response of the microorganism to the heat shock was also examined by analysis of pulse-labeled proteins. Seven heat shock proteins (HSPs) associated with vegetative cells were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Previous studies with C. perfringens indicated that the M r of the bacterial DnaK homologue is approximately 82 kDa [4]. It has been documented that this protein could be an immunodominant antigen, and could play an important role in the pathogenesis of infection by other bacteria [5,17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies with C. perfringens indicated that the M r of the bacterial DnaK homologue is approximately 82 kDa [4]. It has been documented that this protein could be an immunodominant antigen, and could play an important role in the pathogenesis of infection by other bacteria [5,17].…”
Section: Resultsmentioning
confidence: 99%
“…were separately mixed with an equal volume of 4· sample buffer (3% Tris, 20% b-mercaptoethanol, 10% SDS, 0.02% bromophenol blue, and 40% glycerol; pH 6.8), heated at 95°C for 3 min, and then centrifuged to remove any remaining insoluble material. SDS polyacrylamide gel electrophoresis (SDS-PAGE) was performed as previously described [4]. Myosin After electrophoresis, the separated proteins were transferred to nitrocellulose membranes at 360 mA for 4 h at 4°C.…”
Section: Detection Of Immunodominant Stress Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiolabeling of bacterial cells was performed by a modification of the assay described by Heredia et al (1998) For adherence assays, post-confluent cells were used after 2 or 3 days in culture. Cells were dispersed by the addition of 4 ml of trypsin solution (25% w/v, Gibco, BRL, Canada).…”
Section: Radiolabeling Of Bacterial Cellsmentioning
confidence: 99%